Black Elk : a man with a vision - Greene, Carol (Chicago : Childrens Press, 1990)
A simple account of the life of Black Elk, the visionary and Oglala medicine man who had a vision of universal peace and felt that he saw his people's dream die at Wounded Knee.
Includes index.
School Library Journal
Multicultural Review
2.9
K-3
Keywords: Black Elk, -- 1863-1950 -- Juvenile literature; Black Elk, -- 1863-1950.; Oglala Indians -- Biography -- Juvenile literature; Oglala Indians -- Religion -- Juvenile literature; Oglala Indians -- Biography; Indians of North America -- Biography; Black Elk, -- 1863-1950.; Oglala Indians -- Biography; Indians of North America -- Biography